Strategi Bertahan Hidup Mahasiswa IKIP Budi Utomo Malang dengan Menjadi Buruh Bangunan - Winin Maulidya Saffanah; Faizal Kurniawan (Universitas Muhammadiyah Ponorogo, 2021)
Working part-time is a way for some student to make a living. There are several jobs that usually done by students, such as shopkeeper or waiters. One of unsual jobs undertaken by students is construction worker. For IKIP Budi Utomo students from East Nusa Tenggara, part-time job as construction worker is one of their choices. There some reason for this choices, but the main reason is this work financially stable and flexible work time. Being a construction worker is a way they do as survival mechanism. A number of thing such as social capital and social network, play a role in their choice. This study uses a phenomenological qualitative apporoach to expose how survival mechanism is done by students who become construction workers. Informan in this research is IKIP Budi Utomo students from NTT who work as a construction workers. On this research, data collected by using interview, observation, and documentation. From this research, it is known that students utilize social capital in form of netwoeks as survival mechanism for their life and tuition fees. This networks based of similarity origin that helped these students become a construction worker and survive.